2003
DOI: 10.1152/ajpregu.00643.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of AT1 receptor blockade on hepatic redox status in SHR: possible relevance for endothelial function?

Abstract: The study investigated whether the amelioration of endothelial dysfunction by candesartan (2 mg.kg-1.day-1; 10 wk) in spontaneously hypertensive rats (SHR) was associated with modification of hepatic redox system. Systolic arterial pressure (SAP) was higher (P < 0.05) in SHR than in Wistar-Kyoto rats (WKY) and was reduced (P < 0.05) by candesartan in both strains. Acetylcholine (ACh) relaxations were smaller (P < 0.05) and contractions induced by ACh + NG-nitro-l-arginine methyl ester (l-NAME) were greater (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
32
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 46 publications
7
32
0
3
Order By: Relevance
“…The cDNA was stored at -20°C for subsequent analysis. The primer sequences were all obtained from previous published journal articles [35-37] (Geneworks, Australia) (Table 5). Real-time PCR was performed using the iQ5 multicolour real-time PCR detection system (Bio-Rad, USA), with PCR reactions carried out using the iQ SYBR Green Supermix (Bio-Rad, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cDNA was stored at -20°C for subsequent analysis. The primer sequences were all obtained from previous published journal articles [35-37] (Geneworks, Australia) (Table 5). Real-time PCR was performed using the iQ5 multicolour real-time PCR detection system (Bio-Rad, USA), with PCR reactions carried out using the iQ SYBR Green Supermix (Bio-Rad, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The primers were all obtained from previous published sequences and were ordered through Geneworks (Australia): NOX2 [37], p22 phox [35], CuZn-SOD, MnSOD and Ec-SOD [36]. …”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, we found that 2 g but not 1 g of resting tension evidenced reduction of ACh relaxation in SHR compared with WKY. 25 When tension was stable, experiments were initiated by obtaining a reference contractile response to 75 mmol/L KCl. Endothelium-dependent relaxations were studied by evaluating relaxations to ACh (10 Ϫ10 to 10 Ϫ5 mol/L) in noradrenaline precontracted rings (1.5Ϯ0.18 g).…”
mentioning
confidence: 99%
“…Some studies have shown that dietary ALA has a SBP-lowering effect, and the present findings were in accord with this 15,[22][23][24] . Endothelial dysfunction is attributed to a reduction of NO secretion associated with a reduction of endotheliumdependent relaxation and the development of vascular remodeling [25][26][27][28] . In particular, a reduction of vascular relaxation in the large arterial circulation is regarded as a major factor in the development of systolic hypertension 29) .…”
Section: Resultsmentioning
confidence: 99%